Improvement of Pork Quality at Different Values of Pig Productivity - Emelyanov , Alexey; Levkovskaya, Elena; Karatunov, Vyacheslav; Danilenko, Nikita; Ovchinnikov, Dmitry (KnE Life Sciences, 2021)
This article examines how to increase pork meat productivity and quality indicators through the use of crossbreeding. The aim is to increase the meat productivity of animals; reduce losses during production and processing; and improve the criteria for assessing the quality of meat and the organization of its rational use. The purpose of our research is to study the productive quality of the steppe type of pigs, used in the Rostov region in breeding and crossing systems, and the complex of biological and internal indicators in connection with the defects in the quality of pork. Four groups with 16 animals in each were formed: the first group – with the intensive cultivation technology, included pigs of the DM-1 breed, the second – SM-1, the third – the SM-1 × DM-1 crossbreed, the fourth – the DM-1 × SM-1 crossbreed. Analysis of the raw meat showed that the pork had a good ability to emulsify and gel, and had a high nutritional value. The toxicity index in the muscle and fat tissue samples corresponded to the first permissible toxicity group. The study shows the advantages of crossbred individuals over purebred ones, which can be explained by the consequences of heterosis. According to the research results, the use of pig breeding in the industrial production of pork can be recommended in order to improve feedstock and meat productivity, biological and interior indicators, as well as the quality of raw meat. Keywords: pork, crossbreeding, meat productivity, meat quality, steppe type of pigs, interior indicators, fattening qualities, biological and nutritional value of pork